(NsTRANICA L@BWI(B. (NdAMSKOE S^ASTXE(B. (NtEREZA rAKEN(B:s (NrOMANY (B/s - (NzOLQ |(B.s ((NeREWAN(B:s (NaJASTAN(B,s, 1989)
(NrOMANY (B"(NsTRANICA L@BWI(B", "(NdAMSKOE S^ASTXE(B", "(NtEREZA rAKEN(B" (NPRINADLEVAT K ^ISLU NAIBOLEE POPULQRNYH PROIZWEDENIJ ZNAMENITOGO FRANCUZSKOGO PISATELQ(B-(NGUMANISTA(B.s
(NtIRAV(B: 100 000 (N\KZ(B.s
(NiNW(B.: 282709s
Keywords: (NFRANCUZSKAQ LITERATURAs -- (NFRANCUZSKIJ PISATELXs -- (NROMANs